GW24-e1861 Urotensin II inhibited the proliferation of cardiac side population cells in mice during pressure overload by JNK-LRP6 signalling. (1st October 2013) - Chen, Zhidan; Gong, Hui; Li, Yang; Ye, Yong; Zhang, Guoping; Jia, Jianguo; Yang, Chunjie; Zhang, Xiaoyi; Ge, Junbo; Zou, Yunzeng
Abstract : Objectives: Cardiac side population cells (CSPs) are promising cell resource for the regeneration in diseased heart as intrinsic cardiac stem cells. However the relative low ratio of CSPs in the heart limited the ability of CSPs to repair heart and improve cardiac function effectively under pathophysiological condition. Which factors limiting the proliferation of CSPs in diseased heart are unclear. Here, we show that urotensin II (UII) regulates the proliferation of CSPs by c-Jun N-terminal kinase (JNK) and low density lipoprotein receptor-related protein 6 (LRP6) signalling during pressure overload. Methods: Pressure overload was produced by the transverse aorta constriction (TAC). CSPs were isolated and purified by FACS analysis. ERK and JNK were examined by nanofluidic proteomic immunoassay (NIA) method. Results: Pressure overload grealty upregulated UII level in plasma, UII receptor (UT) antagonist, urantide, promoted CSPs proliferation and improved cardiac dysfunction during chronic pressure overload. In cultured CSPs subjected to mechanical stretch (MS), UII significantly inhibited the proliferation by UT. Nanofluidic proteomic immunoassay (NIA) showed it is the JNK activation, but not the extracellular signal-regulated kinas (ERK) signalling, that involved in the UII-inhibited- proliferation of CSPs during pressure overload. Further analysis in vitro indicated UII-induced-phospho-JNK regulates phosphorylation of LRP6 in cultured CSPs after MS, which is important in the inhibitory effect of UII on the CSPs during pressure overload. Conclusions: In couclusion, UII inhibited the proliferation of CSPs by JNK/LRP6 signalling during pressure overload. Pharmcological inhibition of UII promotes CSPs proliferation in mice, offering a possible therapeutic approach for cardiac failure induced by pressure overload.